Producción de látex híbridos acrílicos/alquídicos - Goikoetxea, Monika (2009)
In this work, the production of high solids content hybrid acrylic/alkyd latexes by miniemulsion polymerization is discussed. First, the miniemulsification procedure to achieve colloidally stable hybrid nanodroplets is presented. Next, the efficient nucleation of most nanodroplets during the polymerization, avoiding other nucleation mechanisms is presented. Finally, the key aspects to control the polymer architecture as well as the particle morphology are analyzed.